(untitled) (Global Journal of Human-Social Science, 2015)
This article attempts to study Chinua Achebe’s novel Things Fall Apart from the perspectives put forward in Aime Cesaire’s anti-colonial text Discourse on Colonialism. For this purpose various thematic key-issues found in Discourse on Colonialism are studied first. These thematic key-issues include old African societies, representation, colonial effects, colonial Christianity, decolonization, flaws of civilization etc. In the text Aime Cesaire has strongly dealt with these issues. Then, in this paper each of these issues is thoroughly attempted on the basis of their having treated in Things Fall Apart. Finally, this paper shows that Things Fall Apart can well be analyzed by considering all the thematic concerns voiced by Cesaire.